MOTIVATIONAL MANAGEMENT OF ACADEMIC DECISION-MAKERS AND ITS RELATION TO THE SCIENTIFIC PRODUCTIVITY OF FACULTY MEMBERS IN THE COLLEGES OF PHYSICAL EDUCATION AND SPORTS SCIENCES IN BAGHDAD - Diyar Fakhrulddin Mohammed; Diyar Kareem Najm; Mutasim Abdul Karim Fadhil (Universitas Negeri Jakarta, 2025)
Background. Academic institutions, including universities and colleges, are considered essential pillars upon which modern societies and institutions are built through their administrative progress and development. Objectives. The research aimed to develop two questionnaires on management through motivation and scientific productivity from the perspective of faculty members in the Colleges of Physical Education and Sports Sciences in Baghdad. Method. This was achieved by identifying the sample's responses to the questionnaires and understanding the relationship between motivational management and scientific productivity among faculty members in these colleges. The researchers defined a research population consisting of the Colleges of Physical Education and Sports Sciences in Baghdad Governorate, specifically the Colleges of Physical Education and Sports Sciences (Al-Jadriya, Al-Waziriya, and Al-Mustansiriya), which comprised 502 faculty members. An 85% sample was selected, resulting in a sample size of 427 faculty members. Results. Key findings indicated that universities and colleges should increase financial incentives to support scientific research and motivate faculty members to conduct innovative research. Regular publication of faculty research in peer-reviewed scientific journals also enhances research. Strengthening scientific research enhances its academic reputation. Conclusion. The study recommends expanding continuing education programs for faculty members to improve their skills in scientific research and teaching. Faculty members should be encouraged to publish their research regularly in prestigious international scientific journals with high impact factors and to participate consistently in scientific conferences and seminars. Furthermore, faculty members should work on authoring and updating specialized university textbooks that keep pace with the latest developments in the scientific field.